Organização estrutural da paisagem da Serra da Canastra (MG) - Mariana Fonseca Mauro (2018)
The integrated landscape analysis is a potential tool in environmental planning studies and the protected areas are a suitable context for your application. The selection of the Serra da Canastra National Park (PNSC) as study locus derives from the importance of its environmental framework at the regional and national scale and especially the predominance of individual themes or investigations in specific areas. Thus, this study aims to contribute to the analysis of PNSC throughout its length and complexity, from the elaboration of proposed regional subdivision that includes the characteristics and relationships that exist between spatial units that keep striking homogeneity. The concept of vertical and horizontal structural organization was used in the preparation nine landscape units and a regional section that together allowed the understanding and analysis of the interrelations between the elements in the units proposed. The units were divided in two groups (i) plateaus and (ii) lowlands, due to the strong conditioning of the lithology and structure, and therefore relief, exerts the evolution of the landscape of the area. Added to the analysis of land use, these were the main factors which led to compartmentalization and understanding of the structural organization of landscape of the region.